(untitled) (diségno, 2025)
The contribution proposes a theoretical framework for the analysis of drawing, rooted within the studies of psychology and enriched by significant experiences of visual communication, both contemporary and historical. This approach is justified by considering architectural drawing as a specific declination of drawing understood as a broad language, thus allowing many fundamental observations on the nature, functions and processes of drawing already explored in general contexts to be transferred to the field of architecture. Relevant examples will be shown that illustrate the three main dimensions of drawing as a natural, cultural and universal language, with particular attention to some studies from the 1960s and 1970s that, although partly outdated, are still fundamental in the study of images and drawings. The overall theoretical framework will then be declined in the specific context of architectural drawing, highlighting how it incorporates and utilises the three linguistic dimensions outlined above in an integrated manner. The contribution will conclude with an articulated definition of the distinctive features of drawing understood as a natural, cultural and universal language, laying the foundations for future theoretical and practical reflections on drawing understood as a language.